Research challenges arising from changes in worklife - Rantanen, Jorma (Scandinavian Journal of Work, Environment & Health, 1999)
Great challenges for occupational health research are set by the rapid changes in the world of work as a consequence of globalization, new technologies, demographic workforce changes, fragmentation of enterprises and work contracts, high time pressures, high demands for learning new skills, and growing worker mobility. The occupational health problems are of 2 types, the persistent and reemerging old problems of occupational injuries and diseases and new challenges from psychological stress, musculoskeletal disorders caused by computerized work, cognitive ergonomics in information-intensive work, the work ability of aging workers, and new trends in occupational allergies. The 3 roles of research, improvement of knowledge, improvement of understanding, and support of the development of work conditions in practice, all call for new initiatives in occupational health research. The new comprehensive strategy for the development and promotion of work ability has been found to respond effectively to these new needs.
Keywords: future worklife; information society; occupational health; prevention; promotion; research challenge